Thickness, age and layers data of sediments at IODP Site U1386, U1387, and U1389 - Pan, Jiawei; Stow, Dorrik A V; Smillie, Zeinab; Burgess, Peter (PANGAEA, 2024)
The bi-gradational sequence is recognised as a defining feature of contourite deposition. The present research questions are: In what pattern these bi-gradational sequences are repeated, and what do they represent? What are the climatic and oceanic forces that derive such repetitive pattern? The data provided are geostatistical analyses of the nature and repetition of contourite sequences over 1460 m of section, representing the past 1.4 Ma at two IODP sites in the Gulf of Cadiz, namely Sites U1386 and U1387. A total of 120 and 134 sequences were measured at Sites, respectively. Average sedimentation rates were 33-35 cm ky-1 and 24 cm ky-1, at Sites U1386 and U1387, respectively. The cross-correlation between these two sites shows a good correlation and indicates four main stages. The fluctuation in bottom current velocity and sediment supply has operated at differing timescales over the past 1.4 Ma. The interaction of these controls, rather than one dominant control, causes the varied nature and duration of contourite sequences observed. Shipboard core description and thickness measurements were used as base for the current data. These were verified and, where necessary, minor corrections made during re-logging of all cores used for this study at the Bremen Core Repository. Any modifications to the shipboard core logs were validated by making and examining a further 100 smear slides to measure composition and grain size.
Keywords: AGE; contourite; Contourites; IODP 339; mbsf; sediment; thickness; U1386A; U1386B; U1387A; U1387B; U1389A; U1389B; U1389C; U1389D